2013
DOI: 10.1186/2193-1801-2-376
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl alcohol:starch:carboxymethyl cellulose containing sodium montmorillonite clay blends; mechanical properties and biodegradation behavior

Abstract: The focuses of this study were to investigate the effect of sodium montmorillonite clay (MMT-Na) content on the physical properties and extent of enzymatic hydrolysis Polyvinyl Alcohol (PVA): Starch (S): Carboxymethyl Cellulose (CMC) nanocomposites using enzyme −amylase. The results of this work have revealed that films with MMT-Na content at 5 wt% exhibited a significantly reduced rate and extent of starch hydrolysis. The results suggest that this may have been attributed to interactions between PVA:S:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Starch is hard to process as a pure polymer because its decomposition temperature (Td = 220 º C) is very close to the melting temperature (Tm = 220-240 º C). The presence of many H-bonds between macromolecules also prevents the mobility of these polymeric molecules [20,56,85,86] . Therefore, plasticisers such as water, polyols, glycerol and urea as low molecular weight and low volatile organic agents, can overcome this limitation in addition to increases in flexibility and processability, as well as reductions of brittleness and Tg for native starch by decreasing its intermolecular forces [8,40,83,87] .…”
Section: Pva/starch Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch is hard to process as a pure polymer because its decomposition temperature (Td = 220 º C) is very close to the melting temperature (Tm = 220-240 º C). The presence of many H-bonds between macromolecules also prevents the mobility of these polymeric molecules [20,56,85,86] . Therefore, plasticisers such as water, polyols, glycerol and urea as low molecular weight and low volatile organic agents, can overcome this limitation in addition to increases in flexibility and processability, as well as reductions of brittleness and Tg for native starch by decreasing its intermolecular forces [8,40,83,87] .…”
Section: Pva/starch Blendsmentioning
confidence: 99%
“…This phenomenon depended on starch type and content within the films and took approximately 5-45 days according to environmental conditions [2] . Based on research work by Taghizadeh et al [85] , α-amylose with free mobility first degraded from starch.…”
Section: Biodegradabilitymentioning
confidence: 99%
“…This finding was compared to the study of Koc et al ., who conducted a study with modified CMC and CMC–PVA as a miscible polymer blend; they found that the values of TS and E b for the 50:50 w/w CMC–PVA film to be 7.44 ± 0.69 MPa and 2.42 ± 0.52%, respectively. Taghizadeh et al . investigated the mechanical properties of clay‐incorporated CMC/starch/PVA composites.…”
Section: Resultsmentioning
confidence: 68%
“…Having high aspect ratio, large surface area, and good interfacial properties, layered silicate clay added to a polymer matrix can contribute to significant cost savings as a property enhancer. Clay-containing polymer nanocomposites may offer beneficial properties, such as good mechanical properties, dimensional stability, barrier properties, flame retardant, optical properties, and thermal stability [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%